2020
DOI: 10.3390/polym12040782
|View full text |Cite
|
Sign up to set email alerts
|

Water Absorption and Hygrothermal Aging Behavior of Wood-Polypropylene Composites

Abstract: Environmentally sound composites reinforced with natural fibers or particles interest many researchers and engineers due to their great potential to substitute the traditional composites reinforced with glass fibers. However, the sensitivity of natural fiber-reinforced composites to water has limited their applications. In this paper, wood powder-reinforced polypropylene composites (WPCs) with various wood content were prepared and subjected to water absorption tests to study the water absorption procedure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…The composites showed similar water absorption curves for the entire immersion period. Therefore, the water absorption percentages were considered to be consistent with Fickian diffusion [ 94 , 95 , 96 ]. Moreover, it shows that SD played a profound role on the water absorption behaviour of samples, that is, the water absorption increased with the increase of SD content, which is also consistent with the studies reported by other researchers [ 6 , 97 , 98 , 99 , 100 , 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…The composites showed similar water absorption curves for the entire immersion period. Therefore, the water absorption percentages were considered to be consistent with Fickian diffusion [ 94 , 95 , 96 ]. Moreover, it shows that SD played a profound role on the water absorption behaviour of samples, that is, the water absorption increased with the increase of SD content, which is also consistent with the studies reported by other researchers [ 6 , 97 , 98 , 99 , 100 , 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8b shows the images of WPCs immersed in water. It can be observed that the water absorption rate increased rapidly in the first few days and it slowed down after 8 days [52][53][54]. The water absorption process continued with the prolonged immersion until the specimen reached saturation after 20 days.…”
Section: Water Absorptionmentioning
confidence: 94%
“…Berges et al 27 reported that water aging has a diverse effect on storage modulus and significant decrement in the storage modulus is observed up to the saturated points. Wang et al 28,29 reported the mechanical and viscoelastic properties under hygrothermal aging and the transfer process of water molecules with the Fickiam diffusion model was discussed. The results showed that the diffusion coefficient increased with water uptake and elevated water temperature.…”
Section: Introductionmentioning
confidence: 99%